Research-based learning in biology courses to train students critical thinking skills: Student's perception - Febblina Daryanes; Irda Sayuti (Biosfer: Jurnal Pendidikan Biologi, 2023)
Critical thinking is an ability that has a specific purpose for empowering thinking activities in science education and other disciplines. This study aims to determine student perceptions of applying the Research Based Learning in training student’s critical thinking skills. This research is quantitative descriptive. This type of research is used to analyze data by describe or describe the data that has been collected as it is. The population in this study were all students of biology education, Riau University, while the sample in this study were biology education students in semester 3 of class A who took Biology Learning Media courses. The sampling technique is through purposive sampling. The instrument used is a student response questionnaire and observation sheets that emphasizes the description of the achievement of critical thinking indicators according to Marzano and interview sheets. The questionnaire data were analyzed by calculating the percentage of student responses and the interview data were analyzed qualitatively. The result showed that students gave a positive response to the Research Based Learning in training students’ critical thinking skills by 94% and were in the very good category. The indicators of “open thinking” and “able to provide ideas” are critical thinking indicators that get responses reaching 100%. In line with the observation results that the indicator "able to provide ideas" obtained the highest percentage, namely 88% in the very good category. Each stage in the Research Based Learning in this study provides opportunities for students to develop their critical thinking skills. The results of this study can be used as a reference for developing research-based learning strategies in other subjects.